The Implication of Conversational Implicature Used by Teachers in Offline Classroom Interaction - Suci Pole Mappaita (BATARA DIDI : English Language Journal, 2022)
The purpose of this study was to determine the variation or types of Conversational Implicatures used by teacher interactions in the classroom. This study uses qualitative or descriptive methods and uses them according to the theory of Yule. Data were taken from junior high schools and several teachers as research subjects. The data were analyzed by recording and transcribing and also the data was collected using selection, description, and verification techniques. The author categorizes several dialogues spoken by the teacher which show the types of conversational implicatures in-class interaction. The results showed that there are variation or types of conversational implications in classroom interactions that are used by teachers, including (1) specific implicatures, (2) general implicatures, and (3) scaled implicatures. conversational implications identified by the teacher using specific conversational implicatures of the dominant type.